PDLLA honeycomb-like scaffolds with a high loading of superhydrophilic graphene/multi-walled carbon nanotubes promote osteoblast in vitro functions and guided in vivo bone regeneration - Silva, Edmundo; Vasconcellos, Luana Marotta Reis de [UNESP]; Rodrigues, Bruno V.M.; dos Santos, Danilo Martins; Campana-Filho, Sergio P.; Marciano, Fernanda Roberta; Webster, Thomas J.; Lobo, Anderson Oliveira (Elsevier, 2017)
Herein, we developed honeycomb-like scaffolds by combining poly (D, L-lactic acid) (PDLLA) with a high amount of graphene/multi-walled carbon nanotube oxides (MWCNTO-GO, 50% w/w). From pristine multi-walled carbon nanotubes (MWCNT) powders, we produced MWCNTO-GO via oxygen plasma etching (OPE), which promoted their exfoliation and oxidation. Initially, we evaluated PDLLA and PDLLA/MWCNTO-GO scaffolds for tensile strength tests, cell adhesion and cell viability (with osteoblast-like MG-63 cells), alkaline phosphatase (ALP, a marker of osteoblast differentiation) activity and mineralized nodule formation. In vivo tests were carried out using PDLLA and PDLLA/MWCNTO-GO scaffolds as fillers for critical defects in the tibia of rats. MWCNTO-GO loading was responsible for decreasing the tensile strength and elongation-at-break of PDLLA scaffolds, although the high mechanical performance observed (~ï¿½600ï¿½MPa) assures their application in bone tissue regeneration. In vitro results showed that the scaffolds were not cytotoxic and allowed for osteoblast-like cell interactions and the formation of mineralized matrix nodules. Furthermore, MG-63 cells grown on PDLLA/MWCNTO-GO significantly enhanced osteoblast ALP activity compared to controls (cells alone), while the PDLLA group showed similar ALP activity when compared to controls and PDLLA/MWCNTO-GO. Most impressively, in vivo tests suggested that compared to PDLLA scaffolds, PDLLA/MWCNTO-GO had a superior influence on bone cell activity, promoting greater new bone formation. In summary, the results of this study highlighted that this novel scaffold (MWCNTO-GO, 50% w/w) is a promising alternative for bone tissue regeneration and, thus, should be further studied.
Keywords: Alkaline phosphatase; Graphene oxide; In vivo evaluation; Multi-walled carbon nanotubes; Orthopedics; Poly (D, L-lactic acid)